Tau mutation S356T in the three repeat isoform leads to microtubule dysfunction and promotes prion-like seeded aggregation - Xia, Yuxing; Bell, Brach M.; Kim, Justin D.; Giasson, Benoit I. (Frontiers in Neuroscience, 2023)
Tauopathies are a group of neurodegenerative diseases, which include frontotemporal dementia (FTD) and Alzheimer’s disease (AD), broadly defined by the development of tau brain aggregates. Both missense and splicing tau mutations can directly cause early onset FTD. Tau protein is a microtubule-associated protein that stabilizes and regulates microtubules, but this function can be disrupted in disease states. One contributing factor is the balance of different tau isoforms, which can be categorized into either three repeat (3R) or four repeat (4R) isoforms based on the number of microtubule-binding repeats that are expressed. Imbalance of 3R and 4R isoforms in either direction can cause FTD and neurodegeneration. There is also increasing evidence that 3R tauopathies such as Pick’s disease form tau aggregates predominantly comprised of 3R isoforms and these can present differently from 4R and mixed 3R/4R tauopathies. In this study, multiple mutations in 3R tau were assessed for MT binding properties and prion-like aggregation propensity. Different missense tau mutations showed varying effects on MT binding depending on molecular location and properties. Of the mutations that were surveyed, S356T tau is uniquely capable of prion-like seeded aggregation and forms extensive Thioflavin positive aggregates. This unique prion-like tau strain will be useful to model 3R tau aggregation and will contribute to the understanding of diverse presentations of different tauopathies.